An optimized procedure for direct access to 1H-indazole-3-carboxaldehyde derivatives by nitrosation of indoles. Issue 24 (9th April 2018) - Chevalier, Arnaud; Ouahrouch, Abdelaaziz; Arnaud, Alexandre; Gallavardin, Thibault; Franck, Xavier
Abstract : The nitrosation of indoles under slightly acidic conditions and reverse addition conditions leads to the preparation of the corresponding indazole-3-carboxaldehydes in high yields and greatly minimizes side reactions. Abstract : Indazole derivatives are currently drawing more and more attention in medicinal chemistry as kinase inhibitors. 1 H -indazole-3-carboxaldehydes are key intermediates to access to a variety of polyfunctionalized 3-substituted indazoles. We report here a general access to this motif, based on the nitrosation of indoles in a slightly acidic environment. These very mild conditions allow the conversion of both electron-rich and electron-deficient indoles into 1 H -indazole-3-carboxaldehydes.